Evaluation of latex and of raw natural rubber of rubber tree clones recommended for the São Paulo State, Brazil - Moreno, Rogério Manoel Biagi; Ferreira, Mariselma; Gonçalves, Paulo de Souza; Mattoso, Luiz Henrique Capparelli (Pesquisa Agropecuaria Brasileira, 2003)
The objective of the present paper was to evaluate the parameters of latex and natural rubber from four clones of rubber tree [Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell.-Arg.] planted in large scale in Cambuhy plantations in São Paulo State, Brazil. Latex from 20 trees of each 12-year-old clones viz. GT 1, PB 235, IAN 873 and RRIM 600 following the 1/2S d/3 6d/7. 11m/y. ET 5.0%. Pa 12/y tapping system in the fourth year of yielding. The studied parameters were percentages of dry rubber content (DRC), ashes and nitrogen, Wallace plasticity (PO), plasticity retention index (PRI) and Mooney viscosity (VR). Results indicated a trend of reduction in DRC with decreasing temperatures (r = 0.75). Results of ashes percentages and N percentages indicated a behavior opposite to DRC, increasing with the decreasing temperature along the year. A high correlation value (r = 0.93) was obtained between PO and VR. The high values obtained for PO and VR indicate that the rubber studied should be considered as hard rubbers. The PRI values for these clones were considered low and are associated with a low resistance to thermal degradation. The results obtained indicate a strong influence of climatic conditions on some properties of the lattices and natural rubber for the studied clones. Such parameters suggest an important condition to understand the behavior of these clones.